Analisis Pengaruh Total Aset, Solvabilitas, Opini Auditor, Likuiditas, Dan Ukuran Kap Terhadap Audit Delay (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - Saputri, Melati Qurnia; , Drs. Eko Sugiyanto, M.Si (2016)
Audit Delay is the timespan of completion of the audit conducted by auditors in carrying out the field work. Auditing process requires alot of time because it requires precision in auditing financial statements that indicate the length of the Audit Delay. The purpose of this research is to know total asset, solvability, audit opinion, liquidity, and size of public accountant firms constitute of factors which influence of the audit delay at manufacturing companies registered in indonesian stock exchange. The population is manufacturing company listed in indonesian stock exchange in the period 2012 to 2014. Sampling technique employed in this study is the purposive sampling with the total sample of 201 companies. The method of data analysis used in this research is analysis of multiple linier regression. The results of this research can be concluded that the total asset, solvability, and auditor opinion affect audit delay. While the liqudity and size of public accountant firms hasn't effect on audit delay.